(untitled) (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Firawati I, Murwantoko, Setyobudi E. 2017. Morphological and molecular characterization of hairtail (Trichiurus spp.) from Indian Ocean, southern coast of East Java, Indonesia. Biodiversitas 18: 190-196. The objective of this study was to identify species of hairtails (Trichiurus spp.) which caught from the southern coast of East Java, based on morphology and molecular characters. Three hundred and forty-nine fish samples were collected from two fishing port i.e. Muncar and Prigi. Twenty-two morphometric and four meristic characters were measured from each sample. The result showed that the hairtail samples consisted of two species, T. lepturus and T. brevis based on morphology characters. Based on Principal Component Analysis (PCA) and Discriminant Function Analysis (DFA), these species can be distinguished by the head and caudal character, which the length of an upper jaw and caudal peduncle characters were the main distinguish. Analysis of fragment ( 600 bp) of the mitochondrial DNA encoding 16S rRNA gene showed that T. lepturus samples were 100% genetically identical with T. lepturus while T. brevis samples were 100% identical with T. brevis. Phylogenetic analysis showed that T. lepturus and T. brevis were distinct species while T. lepturus both which caught from Prigi and Muncar were closely related species. The molecular identification can be used to verify the result of morphological identification. Key words: 16S rRNA gene, identification, molecular, morphometric, Trichiurus spp.